The Role of Cooperatives in Encouraging The Implementation of A Green Economy in The Agricultural Sector Based on Local Wisdom in Nganjuk Regency - Bawono, Muhammad; Rahayu, Dwi Puji; Mahendra, Prasetya Tri; Novaliana, Ika (Jurnal Manajemen Bisnis, 2026)
Sustainable agriculture based on a green economy is an urgent need to address the challenges of the climate crisis, land degradation, and farmers' high dependence on chemical inputs. Nganjuk Regency, as an agricultural region, has significant potential to develop environmentally friendly agriculture through the implementation of a green economy. However, adoption of these practices remains limited due to limited access to information, funding, and institutional arrangements. Cooperatives, as people-based economic institutions, play a strategic role in driving this transformation by providing access to financing, training, and facilitating sustainable supply chains. This research aims to analyze the role of cooperatives in promoting the implementation of green economy principles in the agricultural sector, by emphasizing local wisdom as a cultural value embedded in traditional agricultural practices. This study is crucial for strengthening local institutions and addressing the challenges of sustainable development in the agricultural sector. The targeted outputs of this research include publication in accredited national journals and other additional outputs (IPR, international proceedings, and textbooks) as well as providing policy recommendations for local governments in supporting the strengthening of the green economy in Nganjuk Regency. Thus, this research contributes to encouraging sustainable economic growth based on resource efficiency and environmental sustainability.